Benzofuro[2, 3-c]isoquinolines as novel AIEgens: Modulation of AIE characteristics by a single methoxy group. (October 2022) - Kim, Suzi; Park, Jaehyun; Joshi, Dirgha Raj; Lee, Na Keum; Le Bich Pham, Hang; Chung, Linh Khanh; Kang, MinJoo; Kim, Younggwan; Kim, Ikyon; Lee, Jeeyeon
Abstract: Here, we report benzofuro[2, 3- c ]isoquinolines (FiQ ) as novel blue AIEgens, in which a -OMe group substituent plays a crucial role in modulating intermolecular interactions, inducing a marked increase in emission of up to 150- and 460-fold in the aggregate and solid states, respectively. Our single-crystal X-ray diffraction analysis revealed that the edge-to-face interactions among phenyl groups generate tight networks that rigidify the assembled structures, resulting in AIE. Highlights: We developed benzofuro[2, 3- c ]isoquinolines as novel fluorophores with AIE characteristics. Single methoxy group at the C4 position plays a key role in inducing AIE. The solid-state emission significantly increased in the compounds with the methoxy group at the C4 position. Dynamic light scattering (DLS) measurements verified the formation of uniform nanoparticles in aqueous solution.